Cavitation’sEffect on Hydrodynamics of Unmanned Underwater Vehicles - Dharmahinder Singh Chand, Prabhat Singh, Vimal Raj SR, Praveen M (International Journal of Advanced Science and Technology, 2020)
The scope of this project is to design and investigate the hydrodynamic characteristics of the Unmanned Under-Water Vehicle (UUWV) by considering the hydrodynamic phenomenon called cavitation, which has significant effect on the hydrodynamics of the underwater vehicles. In this work unmanned under-water vehicles (UUWV) of about 1metre length with fineness ratio of 6 have been modeled for CFD studies. The models consist of two configurations (without fins and with fins). The models have been meshed and analyzed using the commercial CFD software. The CFD simulation is done for various flow velocities (ranges from 1 to 15m/s). A graph between flow velocity and drag force of the vehicle from computational analysis are plotted. From the results, the hydrodynamic drag force increases parabolically as the flow velocity increases. Computational analysis shows that the drag force on the cavitation model is higher than that of the model without cavitation flow, and the drag increase was found to be 64% for 1m/s. consequently further increase in velocity the percentage of drag increment be further increased (above 64% and so on). Thus the cavitation flow has much effect on drag on the vehicle. Finally the polynomial expressions for drag force in terms of velocity have been interpolated from velocity-drag plot. These polynomials have been interpolated for all configurations. These polynomial expressions can then be used to predict drag values for higher velocities.